2019
DOI: 10.1186/s11671-019-3110-z
|View full text |Cite
|
Sign up to set email alerts
|

Quick Optical Identification of the Defect Formation in Monolayer WSe2 for Growth Optimization

Abstract: Bottom-up epitaxy has been widely applied for transition metal dichalcogenides (TMDCs) growth. However, this method usually leads to a high density of defects in the crystal, which limits its optoelectronic performance. Here, we show the effect of growth temperature on the defect formation, optical performance, and crystal stability in monolayer WSe 2 via a combination of Raman and photoluminescence (PL) spectroscopy study. We found that the defect formation and distribution in monolayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…Considering that defects could decompose TMDs (Fang et al, 2019;Gao et al, 2016), we confirmed the stability of our multi-domain WS 2 monolayer. The confocal Raman and PL and optical microscope images S4 show that the sample is stable over two years without significant decomposition.…”
Section: Resultssupporting
confidence: 76%
“…Considering that defects could decompose TMDs (Fang et al, 2019;Gao et al, 2016), we confirmed the stability of our multi-domain WS 2 monolayer. The confocal Raman and PL and optical microscope images S4 show that the sample is stable over two years without significant decomposition.…”
Section: Resultssupporting
confidence: 76%
“…The full-width half maxima (FWHM) of BP were measured to be 93 meV and that of MoS 2 is 252 meV, which is about 2.7 times higher than that of the BP layer. The lower FWHM of BP compared to that of the MoS 2 is likely to arise from the more tightly bound atoms in BP's puckered structure compared to MoS 2 and the presence of a higher defect density in the latter, compared to BP [42].…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the relationship among the peak intensities of the free (X 0 ), charged (X ‐ ), and bound (X B ) exciton emissions (note that these peaks are located at different energies) can be an indicator of the defect density in monolayer TMDCs. [ 117 , 118 ] In general, a lower intensity for the neutral emission and a higher intensity for the emission of the charged or bound exciton corresponds to a higher number of defects; [ 119 , 120 ] this correlation has been applied to monitor structural quality during optimization of the growth of monolayer TMDCs (Figure 3d ). [ 120 ]…”
Section: Identifying Defects In 2d Materialsmentioning
confidence: 99%
“…[ 117 , 118 ] In general, a lower intensity for the neutral emission and a higher intensity for the emission of the charged or bound exciton corresponds to a higher number of defects; [ 119 , 120 ] this correlation has been applied to monitor structural quality during optimization of the growth of monolayer TMDCs (Figure 3d ). [ 120 ]…”
Section: Identifying Defects In 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation